Fabrication of polydimethylsiloxane (PDMS) microarray devices using spin coating - Tan, Doyle Poh Choon (2019)
The spin coater is widely used in the industry to fabricate thin films. Spin coaters are used in manufacturing industries, and are important in the biomedical industry, as its applications extend to microfluidics. Though commercialised spin coaters are well-established and have great accuracy, the costs of these spin coaters are usually high. Furthermore, current methods for both membrane technologies and microarray technologies are complex and difficult to replicate. A more affordable alternative is thus necessary, to increase the accessibility to such technologies for smaller establishments. Membrane technology is increasing in demand as the filtration process becomes more stringent. Microarray technology is also increasing in demand as more cells are needed to be analysed. The procedures of the current method to manufacture the membrane and microarray are complex. The desire of developing a cost-efficient manufacturing process for microarray devices is in demand. In this report, the acceleration and speed of our homemade spin coater can be adjusted and has good accuracy. It is observed that the homemade spin coater supports the fabrication of the microarray devices. The homemade spin coater is proven to fabricate a 5 micrometre (μm) thick membrane through a cost-efficient process. Cells are seeded into the microarray devices and the results concluded that a 20 μm hole diameter or less would prevent cells or allow a few cells from falling onto the lower layer.